Population pharmacokinetics analysis of intravenous busulfan in Chinese patients undergoing hematopoietic stem cell transplantation. (May 2017) - Wu, Xuemei; Xie, Helin; Lin, Weiwei; Yang, Ting; Li, Nainong; Lin, Shanshan; Yuan, Xiaohong; Ren, Jinhua; Li, Xiaofan; Huang, Xian
Summary: There are several reports describing population pharmacokinetic (popPK) models of busulfan (BU). However, limited information is available in Chinese hematopoietic stem cell transplantation (HSCT) patients. The present study aimed to establish a popPK model of intravenous BU in Chinese HSCT patients for individualized drug therapy. The popPK model of BU was developed from a total of 284 concentration–time points from 53 patients. The effects of demographic and biochemical covariates were investigated by nonlinear mixed effect model (NONMEM) software. Plots, visual predictive check (VPC), bootstrap and normalized prediction distribution error (NPDE) were performed to determine the stability and the reliability of the final model. A one‐compartment model with first‐order elimination process was confirmed as the final structural model for BU. For a typical patient whose body surface area (BSA) is 1.7 m 2, the population typical values of CL and Vd were 11.86 L/h, and 48.2 L, respectively. The result suggested BSA showed significant influence on CL and Vd ( P <.001). Plots revealed the final model was performing a goodness fit. The steady rate verified by bootstrap was 100%, relative deviation was less than 4.00%, estimated value of final model was in the 95% confidence interval (CI). The VPC results showed the observed values were almost all positioned within the 5th and 95th CIs. The mean and variance of the NPDE were 0.0363 (Wilcoxon signed‐rank test, 0.298) and 0.877 (Fisher variance test, 0.134; SW test of normality, 0.108), respectively. The global adjusted P value was 0.305, which indicated that the prediction of the BU popPK model was adequate. A physician‐friendly Microsoft Excel‐base tool was implemented using the final popPK model for designing individualized dosing regimens.